A note on the double dividend hypothesis - Christian M. Scholz (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1996)
This paper tries to clear the confusion in the literature about the potential of environmental tax reforms to yield a double dividend. In opposition to a number of recent papers it is found that the possibility for a double dividend depends largely on the substitutabllity characteristics of taxed commodities and not on the uncompensated elasticities. It is found that a double dividend is possible, if the following conditions are met. First, the initial tax system has to be inefficient from a non-environmental point of view. Second, it is possible to raise the tax on the externality creating commodity and in exchange to reduce the tax on a commodity that is a gross substitute for the externality creating commodity. Third, under the existing distortionary tax system the commodity whose tax is reduced is relatively difficult to substitute through other taxed commodities and hence, easier to substitute through the untaxed numeraire.
Keywords: 330; Umweltabgabe; Steuerreform; Externer Effekt; Steuertheorie; Theorie